283. Antibiotic Utilization for Pneumonia and Other Respiratory Infections in Pediatricians' Offices, Urgent Care Centers, and a Pediatric Emergency Department. (26th November 2018) - Islam, Shamim; Hassinger, Amanda
Abstract: Background: Pneumonia (PNA) and other respiratory infections are common diagnoses in outpatient pediatrics and often result in antibiotic utilization. Professional society guidelines recommend narrow-spectrum agents, namely amoxicillin/ampicillin, as empiric therapy for the majority of pediatric community-acquired pneumonia. In most respiratory infections other than PNA, antibiotics are not indicated. Adherence to PNA guidelines, and antibiotic use for other respiratory infections, in the varied outpatient settings in which children are seen, has not been well characterized. Methods: In a large outpatient sepsis point prevalence study, various data were collected from all patients 0 to 18 years of age seen on September 5, 2016, December 5, 2016, March 6, 2017, and June 5, 2017, in the Emergency Department (ED) of the Women and Children's Hospital of Buffalo, 11 primary pediatric (PMD) offices, and 2 private urgent care centers (UCC) in Buffalo, New York. For this secondary analysis, all children with a provider diagnosis of PNA, bronchitis, bronchiolitis, and upper respiratory infection (URI), were identified. Antibiotic utilization and adherence to Pediatric Infectious Diseases Society PNA (2011) guidelines were analyzed and compared relative to clinical care setting. Results: A larger proportion of children seen in the ED (27.9%) and UCC (25.2%), then PMD (sick) visits (6.1%), were diagnosed with respiratory infections ( P <0.001). PNA specifically was diagnosed in 8% (71/945) of all ED visits. When parenteral agents were given in the ED for PNA, ceftriaxone was most frequent: 58% (10/17) vs. 35% for ampicillin. In PMD and UCC, azithromycin was given in 50% of treated cases (6/12), amoxicillin in 25%, and amoxicillin/clavulanate in 17%. Across the 3 settings, 25% (73/291) of URI received antibiotics; 27% (20/73) did not have a documented co-infection (e.g., otitis media). Conclusion: Despite general awareness of existing PNA guidelines, non-first-line antibiotics are still frequently used across outpatient settings in our area. Also, antibiotics are often given in cases where URI is the primary diagnosis, when a bacterial etiology is unlikely. Pediatric stewardship efforts should further promote available PNA guidelines and avoiding antibiotics for URI, and create educational activities tailored to their local providers. Disclosures: All authors: No reported disclosures.